iPod the missing manual - Biersdorfer, J. D; Pogue, David 1963- (Sebastopol, Calif O'Reilly, 2012)
Explains how to use the portable music player to perform functions including play music, store personal contact and calendar information, download and use applications, and use as a video player
iPod 101 -- Tour the iPod Touch -- Entertain yourself with the iPod Touch -- Get organized with the iPod Touch -- Surf the web and manage email on the Touch -- Add more apps to the Touch -- Tour the iPod Nano -- Tour the iPod Classic -- Tour the iPod Shuffle -- iTunes basics -- iTunes power moves -- The power of playlists -- Shop the iTunes store -- It's showtime : video on the iPod -- Picture your photos on the iPod -- iPod and iTunes out loud -- What to do when your iPod isn't working right
Includes index
Previous ed.: 2011
1
Keywords: iPod (Digital music player)